The lifted veil : and, Brother Jacob / George Eliot ; edited with an introduction and notes by Sally Shuttleworth. - Eliot, George, 1819-1880 (Penguin classics, 2001)
First published in 1859, The Lifted Veil is a dark fantasy woven from contemporary scientific interest in the brain. Published as a companion piece, Brother Jacob is a satirical modern fable which draws parallels between eating and reading.